SIRM-SIAAIC consensus, an Italian document on management of patients at risk of hypersensitivity reactions to contrast media - Maria Teresa Costantino; Laura Romanini; Francesco Gaeta; Fulvio Stacul; Rocco Luigi Valluzzi; Matteo Passamonti; Patrizia Bonadonna; Giovanni Cerri; Stefano Pucci; Paolo Ricci; Eleonora Savi; Michele Galluzzo; et al. (Clinical and Molecular Allergy, 2020)
Abstract Hypersensitivity reactions (HRs) to contrast media (CM) can be distinguished in immune-mediated (including allergic reactions) and non-immune-mediated reactions, even if clinical manifestations could be similar. Such manifestations range from mild skin eruptions to severe anaphylaxis, making it important for radiologists to know how to identify and manage them. A panel of experts from the Società Italiana di Radiologia Medica e Interventistica (SIRM) and the Società Italiana di Allergologia, Asma e Immunologia Clinica (SIAAIC) provided a consensus document on the management of patients who must undergo radiological investigations with CM. Consensus topics included: the risk stratification of patients, the identification of the culprit CM and of a safe alternative by an allergy workup, as well as the use of premedication and the correct procedure to safely perform an elective (i.e., scheduled) or urgent examination. The most important recommendations are: (1) in all patients, a thorough medical history must be taken by the prescribing physician and/or the radiologist to identify at-risk patients; (2) in patients with hypersensitivity reactions to CM, the radiologist must consider an alternative, non-contrast imaging study with a comparable diagnostic value, or prescribe a different investigation with another class of CM; (3) if such options are not feasible, the radiologist must address at-risk patients to a reference centre for an allergy evaluation; (4) if timely referral to an allergist is not viable, it is recommended to use a CM other than the responsible one, taking into account cross-reactivity patterns; in the case of patients with histories of severe reactions, the presence of an anesthesiologist is also recommended and a premedication is suggested.